RANCANGAN PELAKSANAAN LAYANAN BIMBINGAN KLASIKAL DENGAN MENGGUNAKAN METODE DISKUSI UNTUK MENGATASI MASALAH KESULITAN BELAJAR (STUDI ANALISIS DESKRIPTIF TERHADAP PESERTA DIDIK DI KELAS XII IPS 3 SMA N 1 HARAU) - Rifda Kurnia Wati; Fitria Kasih; Triyono Triyono (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research is prompted by issues surrounding learning difficulties, such as students struggling to comprehend lessons, lagging in completing assignments, achieving below-average academic performance, and exhibiting poor study habits. The objectives of this study are: 1) To outline the learning difficulties experienced by students; 2) To devise a plan for implementing classical counseling services utilizing discussion methods to address these learning difficulties. The research methodology employed is descriptive analysis. The study population consists of 32 students, all of whom were included in the sample using the total sampling technique. Data collection was facilitated through a questionnaire, with percentage classification used for data analysis. The findings indicate that: 1) The depiction of students' learning difficulties falls within a relatively high category; 2) A plan for implementing classical counseling services, focusing on the theme of "overcoming learning difficulties," was devised based on identified problems and insights from learning difficulties theory. As a result of this research, it is recommended that counselors employ discussion techniques with Class XII IPS 3 students at Senior High School 1 Harau to address the learning difficulties identified in this study. Implementation of classical counseling services is advised.